Hydroponic Greenhouse Energy Supply Based on Renewable Energy Sources. (2015) - Ronay, Karoly; Dumitru, Cristian-Dragoş
Abstract: The paper presents an approach and a study of hydroponic greenhouses energy supply based on renewable energy sources and independent from the national electric power grid and from the conventional gas heating system. The study presents the hydroponic greenhouse main elements, the technological process, proposed solutions based on renewable energy sources for the electrical and the heating systems and also the management system of such application. The role of the management system is to run the greenhouse efficiently and productively. In the end a financial analysis is presented to analyze the technical-economical index of the greenhouse system.